Analysis of determinants of economic growth using spatial econometrics - Khaitovich, Stefaniia (2024)
This thesis investigates the determinants of economic development in NUTS 2 regions in the 27 countries of the European Union, focusing on spatial dependence, regional disparities and economic convergence. Using GDP data from 235 regions, significant spatial spillovers are confirmed. The analysis identifies 4 key drivers of growth: high-tech employment, life expectancy, share of the service sector and quality of government, while unemployment and agriculture have a negative impact on development. The Spatial Error Model is found to be the most efficient of all the analysed Spatial Models and the results obtained are robust when using different spatial weights matrices. Quantile regression revealed different impacts of GDP determinants depending on the level of development, emphasizing the growing importance of high technology and services in developed regions. Contrary to expectations, there was no evidence of economic convergence, on the contrary, richer regions showed faster development.